A Numerical Technique of Modelling Mortality Rate Intensity for Life Insurance Implementation - Gbenga Michael Ogungbenle; Wipuni.U Sirisena; Ukwu Chukwunenye; Joshua Solomon Adeyele (KEC Journal of Science and Engineering, 2025)
Numerical estimation technique of mortality intensities is integrated into actuarial modelling to ensure cost effective approximations and ascertain benchmarks against which accuracy of mortality table production is verified for applications in life insurance product development. However, some of the governing functional mortality laws analytically formulated as an integral part of underwriting process in life table constructions may not readily have closed form solutions because they are completely intractable. This accounts for why many extant actuarial literatures avoid investigating their asymptotic properties at extreme ages. In this study, the method of successive differencing was deployed to even out errors associated with source vital statistics in order to track the level of any momentous change. The objectives of this study are to produce the instantaneous mortality rate intensities using the Generalized Makeham’s mortality law, to confirm the age at which the probability of death will be 1 and to compute the curve of death. Computational evidence from our result shows that the probability of death for a life aged x approaches 1 at age 120 hence the model supports longevity up to 120 as the omega age. The mortality rate computed is based on the age attained by the insured such that the rate for any given policy at a defined age is independent of the year an insurance